FORMULATION OF LOSSES FOR OIL POLLUTION DUE TO TANKER SHIP ACCIDENT IN THE INDONESIAN LEGAL SYSTEM VALUE OF JUSTICE - Elly Kristiani Purwendah; Aniek Periani (Universitas Pendidikan Ganesha, 2020)
Claims for compensation based on the interests of the marine environment as well as the blue economy concept launched by the government must of course be the basis for the claims of losses given by polluters to restore victims, both human victims (fishermen) and victims of the marine ecosystem, considering that several international instruments have been ratified by the system. national law regarding provisions regulating compensation for oil pollution by tankers. The fair value of compensation for oil pollution due to tanker accidents can be realized by using an economic approach. Analysis of economic theory on law needs to be used, so that the value of justice can be measured properly. Economic concepts, such as the concept of maximization (maximization theory), the concept of equilibrium (equalibirium theory) and the concept of efficiency (efficiency theory) are needed to become a benchmark for the value of justice. The calculation method required for the calculation of claimable compensation is the contingent analysis method, which is a method of calculation based on the assignment of monetary values to environmental goods or commodities, the desire to pay polluters for goods and services produced by natural resources and the environment (willingness to pay). , as well as acceptance to accept something decreasing (willingness to accept).